Pengaruh Latihan Passing Bawah terhadap Kemampuan Bermain Bola Voli Anak SMP N 1 Rambah - Ria Maysari; Ayu Fatmawati; Nabila Cantika Putri; Dewi Sulis Sya'Bani; Maratul Khoiriah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The ability to play volleyball in junior high school students is often not optimal due to the limitations of mastery of basic techniques, especially bottom passing. This research was carried out at SMP N 1 Rambah with the aim of determining the effect of systematic underpassing exercises on improving volleyball playing ability. The research method uses a quasi-experimental experiment with a one-group pretest-posttest design. The research sample consisted of 30 students selected through purposive sampling techniques. The data collection instruments include a lower passing ability test from Nurhasan and an observation test of volleyball playing ability that has been validated. Data analysis was carried out by paired sample t-test after meeting the prerequisite tests for normality and homogeneity. The results showed a significant improvement in students' volleyball playing ability after being treated in the form of programmed underpass training for eight weeks. The value of t is calculated larger than the t table, so the null hypothesis is rejected and the working hypothesis is accepted. These findings confirm that structured, varied, and sustainable underpassing exercises can be used as an effective learning strategy for PJOK teachers in improving the overall quality of student volleyball games.